Rancang Bangun Sistem Informasi Geografis Berbasis Web dan Android untuk Pemetaan Industri Kecil dan Menengah di Kota Mataram - Deo Marta Dipayana; Moh. Ali Albar; Ida Bagus Ketut Widiartha (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
Small and Medium Industries (SMIs) have a very important role as a driver of the economy in Indonesia because SMIs can function as a provider of employment for a number of people who are not accommodated in the formal sector. SMIs also contributes to the formation of Gross Domestic Product (GDP) and as a source of foreign exchange. However, SMIs experienced obstacles in the fields of marketing, business networks, and information technology. In realizing an independent and developing SMIs, a supporting media is needed which can later be useful as a tool to introduce SMIs to the wider community and align it with other business actors. In addition, the government also needs a media that can be used for licensing data collection, taxes, and as a tool to monitor the development of SMIs. In this case a geographic and web-based geographic information system has been built to meet the need for information on SMIs in the city of Mataram. It is hoped that this system can help the community and the government to find out the information needed easily, quickly, and accurately. Based on the results of the Mean Opinion Score, it shows that the average rating of respondents of website users on the system agrees and strongly agrees to agree worth 67.50%. While the average rating of respondents of mobile users to the system agree and strongly agree is worth 78.33%.